The Efficiency of Indonesian and Malaysian Sharia Bank in the Shadow of Covid-19 Pandemic: DEA Window Analysis - Ihsanul Ikhwan Ikhwan; Ririn Riani Riani (Faculty of Economics and Management, 2022)
The Pandemic conditions can lead to various problems that can trigger financial distress and inefficiency, especially in the banking sector. In recent decades, there has been a rapid increase in sharia banking, and the importance of this sector to the economies of several countries. The assessment of sharia bank's efficiency will become important as efficiency reflects the banks' performance. This study aims to analyze the stability of sharia bank efficiency in Indonesia and Malaysia using the Data Envelopment Analysis (DEA) dan DEA Window method. This study uses 2015 to 2020 as a research period, especially to look at the stability efficiency of Indonesia and Malaysian Sharia Bank in the Covid-19 pandemic era. The result showed that Indonesia is better than Malaysia in terms of efficiency stability. However, both show a similar pattern, where there is a decrease in the average level of efficiency during the Covid-19 pandemic. From the perspective of efficiency stability analysis through several summary statistics such as its Standard Deviation (SD), Long Distance per Period (LDP), and Long Distance per Year (LDY), the sharia bank with the most relatively stable value of efficiency scores is Maybank Islamic Berhad, then followed by BRI Syariah and BSM.